Гарлемський ренесанс як пролог мультикультуралізму - Шимчишин, М. (Питання літературознавства, 2009)
Значна увага статті зосереджена на передумовах виникнення ідеї багатокультурності. Авторка звертається до епістеми гетерогенної ідентичності. Крім того, розглядається Негритянське відродження як потужний голос Іншого в американській культурі початку ХХ століття. We all choose certain categories and organize ourselves around particular discourses. It means that everyone is engaged in identity politics (gender, class, origin etc.). Discussions of how we shape (are shaped) ourselves, why we prefer certain narratives over the others did not begin in the last century or nowadays. They were extended in ancient times. Every nation or race had had some landmark events that helped it to find organizing principles and define it as a separate community. Harlem Renaissance was a cultural movement that aimed to form „New Negro Identity”. Its artists, writers and activists consciously positioned themselves as creators of The New Negro. Therefore the study of this cultural phenomenon will help to clarify what strategies have been used to construct the identity of African Americans. Therefore the main objective of the article is to find out what discourses were taken as the most representative of the African American experience and later constituted the cornerstone of Blackness. The author aims to investigate why certain African American voices or images were privileged and how it influenced the concept of Black identity.